Does Low Job Satisfaction Lead to Job Mobility? - Nicolai Kristensen; Niels Christian Westergård-Nielsen (Institute for the Study of Labor (IZA), 2004)
This paper seeks to analyse the role of job satisfaction and actual job change behaviour. The analysis is based on the European Community Household Panel (ECHP) data for Danish families 1994-2000. The results show that inclusion of job satisfaction, which is a subjective measure, does improve the ability to predict actual quit behaviour: Low overall job satisfaction significantly increases the probability of quit. Various job satisfaction domains are ranked according to their ability to predict quits. Satisfaction with Type of Work is found to be the most important job characteristic while satisfaction with Job Security is found to be insignificant. These results hold across age, gender and education sub-groups and are opposed to results for UK, where job security is found to be the most important job domain. This discrepancy between UK and Denmark might be due to differences in unemployment insurance benefits and indicates that there are ?invisible? benefits inherited in the welfare state insurance system because employees in Denmark don?t worry about job security.
Keywords: J60; J30; J28; M50; 330; job satisfaction; quits; personnel economics; Arbeitszufriedenheit; Arbeitsmobilität; Schätzung; Dänemark